THE APPLICATION OF THE CAPITAL ASSET PRICING MODEL (CAPM) METHOD AS A BASIS FOR INVESTMENT DECISION MAKING IN LQ45 INDEX STOCKS ON THE INDONESIA STOCK EXCHANGE FOR THE PERIOD 2019-2023 - Wahyuni, Nurul; Rismala; Husain, Saddan (Islamic Financial And Accounting Review, 2025)
In the world of investment, investors must be able to identify investment opportunities that provide returns so that they can generate optimal levels of return with minimal risk. This study aims to analyze stock investment decisions using the Capital Asset Pricing Model (CAPM) using the LQ45 Index as a market proxy. This type of research is descriptive research with quantitative methods. The data source used is secondary data, namely monthly closing price data. The sampling in this study was determined using purposive sampling, out of 45 companies included in the LQ45 index, only 23 companies met the criteria and became a research sample. The data analysis method was used using the Capital Asset Pricing Model (CAPM) method to classify undervalued and overvalued stocks using Microsoft Excel 2016. The results of the calculation of the rate of return of individual shares (Ri) resulted in an average of 0.00506, with the largest return owned by ANTM shares and the lowest by INDF shares. The average systematic risk is worth more than 1, which is 1.25, so in general, the 23 shares of the companies used as research samples have high systematic risk and tend to be active in responding to market price changes. Based on the data analysis, there is a nonlinear relationship between systematic risk (β) and the expected rate of return on shares [E(Ri)]. Of the 23 company stocks that were the research sample, there were 12 company stocks that were included in the undervalued category, namely, ADRO, ANTM, BBCA, BBNI, BBRI, BBTN, BMRI, CPIN, EXCL, INCO, INKP, ITMG. Meanwhile, there are 11 company stocks that are in the overvalued category, namely, ASII, ICBP, INDF, INTP, KLBF, PGAS, PTBA, SMGR, TLKM, UNTR, UNVR.